1989
DOI: 10.2466/pms.1989.68.3c.1091
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Learning Styles: Their Link to Academic Performance, Sex, Age, and Academic Standing

Abstract: The primary purpose of this investigation was to ascertain whether students' learning styles affected performance in remedial courses. The study also investigated whether learning styles differed in terms of age, sex, and class-standing in a university setting While type of learning style did not differ with respect to class-standing or sex, type of learning style differed significantly with respect to age. Most importantly, type of learning style significantly influenced grade point average in remedial course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Several studies have produced findings that indicated differences in academic performance by students manifesting different learning-styles (O'Brien, 1994). Ginter, Brown, Scalise, and Ripley (1989) reported that learning-style type did not differ in relation to university class standing or gender, but differed significantly in relation to age. Their most substantive finding was that type of learning style significantly affected students' grade point averages in remedial courses.…”
Section: Learning Style and Achievementmentioning
confidence: 92%
“…Several studies have produced findings that indicated differences in academic performance by students manifesting different learning-styles (O'Brien, 1994). Ginter, Brown, Scalise, and Ripley (1989) reported that learning-style type did not differ in relation to university class standing or gender, but differed significantly in relation to age. Their most substantive finding was that type of learning style significantly affected students' grade point averages in remedial courses.…”
Section: Learning Style and Achievementmentioning
confidence: 92%
“…Certainly the way they are conceived and measured is primarily attributable to their subdisciplinary origin in social, clinical, personality, or cognitive psychology. Researchers in the last discipline tend to focus on perception, attention or memory factors and hence conceive of cognitive styles in these terms (Ginter, Brown, Scalise, & Ripley, 1989) whereas the former approaches tend to focus on the inter-and intrapersonal function and consequences of adopting any particular style. Indeed, the area could do with a little conceptual and methodological housekeeping to exarnine common themes in the myriad of measures that exist.…”
Section: Information Gathering and Evaluationmentioning
confidence: 99%
“…The other two studies addressed freshmen to seniors over a shorter duration using multiple universities or majors. Ginter et al (1989) reported that learning style types did not differ in relation to university class standing but varied significantly in regard to age. This may explain the unimodal nature seen in Zollinger and Martinson.…”
Section: Discussionmentioning
confidence: 96%
“…Investigators explored gender differences in learning styles and how this variable relates to academic performance (Kulturel-Konak et al, 2011;Lau & Yuen, 2010;Wehrwein et al, 2007). Relationships between learning style, class standing, and age were also investigated (Ginter et al, 1989), and researchers demonstrated the connection between learning style to academic performance, showing that students with learning styles that are at odds with their pedagogical environment can be at a disadvantage (Jafre et al, 2011;Kvan & Jia, 2005;Nuzhat et al, 2013). Slaats et al (1999) noted that understanding students' learning styles has many possible education applications.…”
Section: Learning Stylesmentioning
confidence: 99%